PERENCANAAN STRATEGI BISNIS DAN PENGEMBANGAN MANAJEMEN MEREK DI TOKO SUMBER REJEKI BAN REMBANG - Wijaya, William; Surjani, Rosita Meitha; Lianto, Benny (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2012)
Good business strategy planning and good development brand management is needed by Toko Sumber Rejeki Ban Rembang. To determine suitable business strategy that can be applied to this business, strategy formulationcan be use to do analysis that covering the input stage, phase matching and decision stage. At the input stage, the results of the IFE matrix produces a score of 2.59, this score can be interpreted that the store already has a good performance. And for the EFE matrix, the result score is equal to 3.16, this score can be interpreted that the store response to external factors that exist. Furthermore, fromthe obtained results that the making of CPM Toko Sumber Rejeki Ban Rembang far superior than both its competitors, namely Toko Maju Ban and Toko Teguh Laksana Ban. In the matching stage, GSM shows the results that Toko SumberRejeki Ban Rembang in the quadrant I, because this store has a high market growth and has a stong competitive potition too. And in IE·Matrix result shows that Toko Surnber Rejeki Ban Rembang in the cell II, which mean that this store has to grow and evolve. The next step is making SWOT Matrix, which produce the type of strategic alternatives based on the types of strategies are suggested. Those strategic alternative will be grouped according to the types of strategies that exist, and then will selected three alternative strategies for an alternative site in the strategic decision·making QSPM on stage. The results showed that QSPM Toko Sumber Rejeki Ban Rem bang suitable when using the type of market penetrationstrategies. This type of strategy could be strengthened by implementing marketing strategy includes the creation of strategies STPD and 8P. Once you know what the business strategy is matched, then the next step is how to improve the management of existing brands in the store, that is by measuring the brand equity of existing scoring at this store. Scoring brand equity measurement results showthat the brand equity that existed at this store is high, with the score at 3. That´s because the scores on each dimension that is on brand equity owned stores alsohave a score high at each 3. These dimensions include the brand awareness, brand associations, perceived quality, and brand loyalty. After learning that the value of brand equity in the Toko Sumber Rejeki Ban Rembang is high, then the next step is how to maintain brand equity values, one of which is the manufacture of brand elements and other promotional media.